The Effect of Financial Ratios on Financial Distress Conditions is Moderated by Profitability Ratios - Apasya, Trida; Machmuddah, Zaky; Sumaryati, Anna (Universitas Dian Nuswantoro Semarang, 2023)
This study aims to examine the effect of financial ratios moderated by profitability ratios on the financial distress of transportation and logistics sector companies listed on the IDX for 4 consecutive years in the 2018-2021 period. The independent variables are proxied by CR (liquidity), DAR (leverage), SG (growth), and the addition of TATO (activity). In addition, ROA is a proxy for the profitability variable which is the moderating variable. The Z-Score (Altman) is a proxy for financial distress as the dependent variable. This study selected companies in the transportation and logistics sector for the 2018-2021 period as a population with a sample size of 18 companies in the transportation and logistics sector that met the criteria. Logistic regression analysis was used as an analytical technique in this study. The results of his research inform that CR, DAR, and TATO have a significant influence on the occurrence of financial distress. Meanwhile, SG did not significantly affects the occurrence of financial distress. In addition, ROA can moderate the effect of SG and TATO on the occurrence of financial distress. However, ROA is unable to moderate the effect of CR and DAR on the occurrence of financial distress.